2013
DOI: 10.5009/gnl.2013.7.5.546
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Therapy for Helicobacter pylori Infection in Korea: Systematic Review and Meta-Analysis

Abstract: Background/AimsSequential therapy (ST) for Helicobacter pylori infection in countries other than Korea has shown higher eradication rates than triple therapy (TT). The aim of this study was to evaluate the efficacy of ST in Korea by performing a meta-analysis.MethodsWe performed a comprehensive literature search on the efficacy of ST as a first-line therapy. The odds ratios (ORs) of eradicating H. pylori infection after ST compared with TT were pooled. Pooled estimates of the eradication rates of ST and TT wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Reasonable treatment regimens need to attain H. pylori eradication rate of higher than 80.0% by intention to treat (ITT) analysis, and higher than 90.0% by per protocol (PP) analysis [15, 16]. Several previous meta-analyses reported the superiority of SET than TT [17, 18], whereas other studies revealed conflicting results [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Reasonable treatment regimens need to attain H. pylori eradication rate of higher than 80.0% by intention to treat (ITT) analysis, and higher than 90.0% by per protocol (PP) analysis [15, 16]. Several previous meta-analyses reported the superiority of SET than TT [17, 18], whereas other studies revealed conflicting results [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…This is the cause of geographical variation in eradication rates from the sequential regimen [33]. In Korean meta-analysis, pooled estimates of the ITT and PP eradication rate were 79.4% (95% CI, 76.3% to 82.2%) and 86.4% (95% CI, 83.5% to 88.8%), respectively, for patients receiving the 10-day sequential treatment [29]. However, fair efficacy of the sequential regimen cannot be further guaranteed because of the increase in primary and secondary antibiotic resistance to clarithromycin in H. pylori in Korea is ongoing.…”
Section: Discussionmentioning
confidence: 97%
“…Based on previous studies about SST in Korea and LST, we assumed that SST and LST would achieve eradication rates of 79.3% and 96.0%, respectively [25,29]. Thus, to determine the 17% difference, 99 patients in each group were required with a power of 90% at a 5% significance level, with the expectation of a drop-out rate of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…It is an acceptable treatment option in countries other than Turkey and Latin American countries [25,26]. It is an acceptable treatment option in countries other than Turkey and Latin American countries [25,26].…”
Section: Discussionmentioning
confidence: 99%